2007
DOI: 10.1002/cncr.22921
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of bortezomib therapy in multiple myeloma: A single‐center experience and review of the literature

Abstract: BACKGROUND. Bortezomib is active in heavily pretreated multiple myeloma patients; the dose‐limiting toxicity is peripheral neuropathy (PN). METHODS. The authors retrospectively reviewed the incidence, severity, and risk factors for PN in 78 patients who received bortezomib. The median age was 57 years (range, 33–80 years), 62% of patients were men, and 37% of patients were African Americans. Seventeen patients (22%) had diabetes mellitus (DM), and 66 patients (85%) had received thalidomide. Before bortezomib t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
162
5
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(178 citation statements)
references
References 26 publications
9
162
5
2
Order By: Relevance
“…PN is the main dose-limiting toxicity associated with bortezomib therapy (18). The results of the present study indicated that no differences were found between the occurrence of PN in patients with the CYP2C19 genotype and those with the CYP3A4 genotypes.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…PN is the main dose-limiting toxicity associated with bortezomib therapy (18). The results of the present study indicated that no differences were found between the occurrence of PN in patients with the CYP2C19 genotype and those with the CYP3A4 genotypes.…”
Section: Discussioncontrasting
confidence: 52%
“…CYP3A4 * 1 was considered to be the wild type genotype. In a previous study, * 18 was only reported in Asian populations, and had a frequency of 2% (12). The frequency of the CYP3A4 * 18 allele in the present study was 0.9%.…”
Section: Discussionmentioning
confidence: 96%
“…The reported incidence is 1% to 20% in untreated patients with MM and 37% to 83% in previously treated individuals; neurophysiologic evidence of neuropathy may be detected in 11% to 52% and 39% to 46% of these populations, respectively. [1][2][3][4][5][6] Risk factors for PN include treatment-specific characteristics, such as therapy duration, dose intensity, and cumulative dose, and patient-specific factors, such as age, comorbidities (e.g., diabetes mellitus, alcoholism), and the presence of preexisting neuropathy. The incidence of thalidomide-induced PN varies among different patient populations, treatment regimens, and diagnostic criteria, but estimates range from 37% to 83%.…”
Section: Peripheral Neuropathymentioning
confidence: 99%
“…Therapeutic Intervention: Nonpharmacologic management of sensory PN symptoms or neuropathic pain may involve the use of daily vitamins and nutritional supplements (e.g., multi-B complex vitamins [B 1 , B 6 , B 12 ], folic acid, magnesium, potassium, vitamin E, acetyl l-carnitine, α-lipoic acid, l-glutamine; see Table 3 for dosing), emollient creams (e.g., cocoa butter, menthol, and eucalyptus-based creams), and physical therapy, as well as therapeutic massage.…”
mentioning
confidence: 99%
“…When used after exposure to thalidomide, bortezomib, or vincristine, lenalidomide can cause mild to severe CIPN [6]. The incidence rate of bortezomib-induced CIPN in patients with newly diagnosed MM ranged from 11% to 81% [7][8][9], and rigorous measures are required to control bortezomib-induced CIPN as demonstrated by its severity-dependent dosimetry guidelines [10]. Given the risks involved, it is crucial to assess the relevance of CIPN, identify high-risk factors for CIPN prior to administering known neurotoxic agents, and conduct routine CIPN monitoring and medical interventions to alleviate CIPN symptoms in accordance with therapy plans.…”
Section: Introductionmentioning
confidence: 99%